Population dynamics and migration of cowpea pests in northern Nigeria: implications for integrated pest management - Bottenberg, H.; Tamo, Manuele; Arodokoun, D.; Jackai, L.E.N.; Singh, B.; Youm, O. (1997)
The population dynamics of major cowpea pests was studied in northern Nigeria during 1992-95 in both the wet and dry seasons. Rainfall cowpea is grown as a subsistence crop, mixed at low densities with cereals. Dry-season cowpea is irrigated or grown on residual moisture in monocultures as a cash crop. Light-trap monitoring and sampling of cowpea fields, throughout the wet and dry seasons, showed that Manica \iirata (previously M. testulalis) does not occur during the dry season in northern Nigeria, even if cowpea is present. Corroborative data from more southern locations within the study region showed that Mariica is a migratory pest, which survives the dry season on alternate hosts in the more humid south and migrates to the north following the pattern of rainfall and cowpea cultivation. Similarly, populations of Megalurothrips sjosledri and Clavigralla tomentosicollis are very low on cowpea during the dry season but develop rapidly during the rainy season. Aphids and Lycaenids are present year round but predominate during the dry season. The importance of seasonal changes in the pest complex and cropping system for integrated pest management (IPM) of cowpea is discussed.